2004
DOI: 10.2460/ajvr.2004.65.1185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a long-acting formulation of ceftiofur crystalline-free acid for the treatment of naturally occurring infectious bovine keratoconjunctivitis

Abstract: A single dose of CCFA administered into the posterior aspect of a pinna had a positive treatment effect against naturally occurring IBK in calves with corneal ulcerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
(3 reference statements)
1
25
0
Order By: Relevance
“…The pinna site was chosen due to the reduced risk for tissue residue and the lower potential for injection‐site trimming at slaughter. Concentrations of ceftiofur metabolites in plasma have been shown to remain well above published M bovis modal MIC values for more than 7 days when administered via this particular route 12,32,33 . A single dose of CCFA (6.6 mg of ceftiofur equivalents/kg, SC) proved effective in the treatment of IBK in beef calves, resulting in shorter mean healing times, smaller corneal ulcer surface areas, amelioration of ocular discharge and photophobia, and a 50% increase in the percentage of calves healed by day 14 32 .…”
Section: Systemic Treatmentmentioning
confidence: 71%
“…The pinna site was chosen due to the reduced risk for tissue residue and the lower potential for injection‐site trimming at slaughter. Concentrations of ceftiofur metabolites in plasma have been shown to remain well above published M bovis modal MIC values for more than 7 days when administered via this particular route 12,32,33 . A single dose of CCFA (6.6 mg of ceftiofur equivalents/kg, SC) proved effective in the treatment of IBK in beef calves, resulting in shorter mean healing times, smaller corneal ulcer surface areas, amelioration of ocular discharge and photophobia, and a 50% increase in the percentage of calves healed by day 14 32 .…”
Section: Systemic Treatmentmentioning
confidence: 71%
“…50 In that study a control group of calves were administered vehicle alone (control group). This treatment resulted in a 4 fold increased odds of corneal ulcer healing by 14 days as compared to control group calves and results supported that CCFA was effective against naturally occurring IBK.…”
Section: Parenteral Ceftiofurmentioning
confidence: 99%
“…In one study, bacteria that were cultured from IBK-associated corneal ulcers were identified as Gram negative cocci in ∼46% of ulcers, while only ∼21% of ulcers were M. bovis positive (Dueger et al 2004). Gram negative cocci from that study were subsequently identified as M. bovoculi (Angelos et al 2007c).…”
Section: Introductionmentioning
confidence: 99%